Chronic vs. Short-Term Acute O3 Exposure Effects on Nocturnal Transpiration in Two Californian Oaks - N. E. Grulke; E. Paoletti; R. L. Heath (The Scientific World Journal)
We tested the effect of daytime chronic moderate ozone (O3) exposure, short-term acute exposure, and both chronic and acute O3 exposure combined on nocturnal transpiration in California black oak and blue oak seedlings. Chronic O3 exposure (70 ppb for 8 h/day) was implemented in open-top chambers for either 1 month (California black oak) or 2 months (blue oak). Acute O3 exposure (~1 h in duration during the day, 120–220 ppb) was implemented in a novel gas exchange system that supplied and maintained known O3 concentrations to a leaf cuvette. When exposed to chronic daytime O3 exposure, both oaks exhibited increased nocturnal transpiration (without concurrent O3 exposure) relative to unexposed control leaves (1.8× and 1.6×, black and blue oak, respectively). Short-term acute and chronic O3 exposure did not further increase nocturnal transpiration in either species. In blue oak previously unexposed to O3, short-term acute O3 exposure significantly enhanced nocturnal transpiration (2.0×) relative to leaves unexposed to O3. California black oak was unresponsive to (only) short-term acute O3 exposure. Daytime chronic and/or acute O3 exposures can increase foliar water loss at night in deciduous oak seedlings.